Poverty and Economic Decision-Making: Evidence from Changes in Financial Resources at Payday - Carvalho, Leandro S.; Meier, Stephan; Wang, Stephanie W. (American Economic Review, 2016)
We study the effect of financial resources on decision-making. Low-income U.S. households are randomly assigned to receive an online survey before or after payday. The survey collects measures of cognitive function and administers risk and intertemporal choice tasks. The study design generates variation in cash, checking and savings balances, and expenditures. Before-payday participants behave as if they are more present-biased when making intertemporal choices about monetary rewards but not when making intertemporal choices about non-monetary real-effort tasks. Nor do we find before-after differences in risk-taking, the quality of decision-making, the performance in cognitive function tasks, or in heuristic judgments.